The Mediating Effect of Physical Exercise and Socially Learned Helplessness in The Relationship Between Parental Control and Mobile Phone Addiction - Chen Tingwei; Wang Haiqing; Yang Xintian; Chang Zhai; Xiya Li; Haoliang Mai; Weilin Su, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study investigated the impact of parental control on mobile phone addiction, exploring the mediating roles of physical exercise and socially learned helplessness. Questionnaires were used to collect data on parental control (including psychological control and behavioral control), mobile phone addiction, physical exercise, and learned helplessness from university students. After screening for validity, 500 valid questionnaires were obtained, resulting in an effective rate of 98.43%. Of these participants, 252 were male (50.40%) and 248 were female (49.60%). Data were analyzed using SPSS 26.0 and the PROCESS plugin. The results showed significant correlations among parental control, physical exercise, socially learned helplessness, and mobile phone addiction (ps < 0.001). Parental control and its dimensions directly predicted mobile phone addiction (ps < 0.001). Physical exercise and socially learned helplessness acted as parallel mediators between parental psychological control and mobile phone addiction, while they acted as serial mediators between parental behavioral control and mobile phone addiction. There was no significant mediation effect of physical exercise on the relationship between overall parental control and mobile phone addiction; however, parental control had a significant predictive effect on physical exercise. Socially learned helplessness mediated the effect of overall parental control on mobile phone addiction. These findings suggest that parents and schools should address students' behavioral problems not only from the perspective of technological advancements and individual factors but also consider other factors such as parental control and socially learned helplessness when developing intervention programs. Parents should adopt a correct educational perspective and gradually release their control when appropriate. Schools, teachers, and parents should emphasize the importance of physical exercise, provide more opportunities for sports activities, and guide students in recognizing the significance of physical exercise.